Pubertal arrest secondary to untreated giant prolactinoma - Sarmiento-Piña, Maira (2024)
The most common pituitary tumors are prolactinomas which are rarely found inchildren and adolescents. Similarly, hyperprolactinemia is a rare endocrinopathy inchildhood. The hypersecretion and production of prolactin as well as the compressionproduced by prolactinoma compromises the functioning of the hypothalamicpituitary-ovarian axis, probably due to impaired gonadotropin pulsatility, togetherwith the presence of adrenal and thyroid insufficiency. This functional syndromemay cause delayed puberty, primary or secondary amenorrhea, galactorrhea, andpubertal arrest. The onset of telarche and puberty is age appropriate, but arrest ofpubertal development before menarche is a rare disorder known as pubertal arrest.Dopaminergic agonists are the first choice of treatment. A case of pubertal arrestsecondary to untreated giant prolactinoma is presented.